Occurrence of Skin Abscess and Sensitivity Pattern of Associated Bacterial Organisms in Pigs on Ifelodun Farm Settlement, Ogun State, Nigeria (2016)
Pigs are relatively prone to abscess formation especially in the skin. This study was designed to assess the occurrence of skin abscess in pigs on the Ifelodun farm settlement in Ogun state, South-West Nigeria and evaluate the antibiotic sensitivity pattern of bacterial organisms isolated from pus samples from the abscesses. A total of 2,909 pigs from 104 randomly selected farms on the Ifelodun farm settlement were physically examined. The anatomic locations of gross swellings on the skin were noted. Diagnosis of skin abscess was arrived at after palpation and aspiration of content. Pus samples from 14 intact abscesses were collected aseptically for isolation and sensitivity using standard cultural and disc diffusion method respectively. Data were analysed using descriptive statistics. 26 (0.89%) of the 2,909 pigs examined across 22 (21.2%) farms out of 104 farms surveyed were affected. The anatomic distribution of the abscesses includes 43.3%, 6.67%, 16.67% and 33.33% on the neck, forelimbs, trunk, and hind limbs respectively. None was observed on the head. 10 bacterial species were isolated from the 14 tested isolates with Arcanobacterium pyogenes (57.1%), Staphylococcus aureus (42.8%) and Escherichia coli (35.7%) being most frequently isolated. Antibiotic sensitivity profile varied with more isolates being sensitive to Erythromycin, Tetracycline, Gentamicin, and Chloraphenicol for gram positive bacterial species and Ceftazidine, Cefuroxime, Gentamicin and Augmentin for gram negative species. Swine skin abscess affects various body regions in pigs on Ifelodun pig farm settlement. The neck and hind limbs were mostly affected likely due to poor injection practices. Based on availability of veterinary preparation readily available in the Nigerian market, Gentamicin, Tetracycline and Erythromycin remain viable options for post-surgical management of the abscesses while Chloramphenicol should be avoided due to its deleterious effect on humans. Antibiotic sensitivity is recommended in cases of recurring skin abscesses in a pig or herd.